Effects of Nitrogen Forms on Soil Enzyme Activities in a Saline‐Alkaline Grassland - Jiangqi Wu; Haiyan Wang; Guang Li; Fujiang Hou; Guorong Xu (Ecology and Evolution)
ABSTRACT Global climate change and agricultural practices have increased atmospheric nitrogen (N) deposition, significantly affecting the nitrogen cycling process in grasslands. The impact of different N forms on key soil enzyme activities involved in N nitrification, particularly in the saline‐alkali grasslands of the Hexi Corridor, using natural grassland as a control (CK) and adding three N treatments: inorganic N (IN), organic N (ON) and a mixed N treatment (MN, with a 4:6 ratio of organic to inorganic N). Our study assessed the effects of these N forms on soil properties and enzyme activities crucial for N cycling. The findings indicate that different N forms significantly enhance soil mineral N content, with ON treatment leading to the highest increases in nitrate and ammonium content 92.44% and 35.6%, respectively, compared to CK. Both IN and ON treatments significantly boosted soil nitrate reductase and urease activities (p < 0.05), while MN treatment decreased nitrate reductase activity, with ON treatment showing the greatest sensitivity to enzyme activity changes. Soil pH slightly increased with N addition, but soil nitrite reductase activity remained relatively unchanged (0.372–0.385 mg g−1). Correlation analysis revealed that soil mineral N content and pH are key regulators of enzyme activities in saline‐alkaline grasslands. These results suggest that different N forms should be considered in nutrient cycling models, with organic N addition potentially enhancing soil N conversion and mitigating nutrient limitations in grassland ecosystems.